FACTORS INFLUENCING THE WORK PERFORMANCE OF EMPLOYEES AT TEIJIN (THAILAND) IN THE TEXTILE INDUSTRIES SECTOR - Thetsakal, Apiwut; Someran, Laddawan (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
The aims of this study included achievement of two primary objectives: (1) to examine the levels of employee perceptions regarding work motivation, innovative work behavior, and job performance at Teijin (Thailand) Co., Ltd., which operates in the textile industries sector; and (2) to investigate the effects of work motivation and innovative work behavior on employee job performance. A quantitative research method was employed in this study with data collected from a total of 231 employees using a structured questionnaire specifically designed to measure the relevant variables. The collected data were analyzed through the use of descriptive statistics and multiple regression analysis. According to the results, the employees reported a high level of work motivation, with the highest mean score observed in the area of job responsibility. Likewise, the overall level of innovative work behavior was also rated as high, with idea implementation being the most prominent component. Job performance among employees was also found to be high overall, with the highest score reported in the area of the speed of work. The hypothesis testing revealed that specific work motivation factors, namely achievement, the nature of the work, and opportunities for advancement, had a statistically significant influence on employee job performance at the .01 level. Furthermore, innovative work behavior factors such as idea generation, idea support, and idea implementation also showed statistically significant impacts on performance at both the .05 and .01 levels. These findings underscore the importance of promoting both employee motivation and innovative behavior within the organization and also provide essential insights into the design and implementation of strategies to improve job performance that can be applied in human resource management. Ultimately, these results can be utilized as a practical guideline to support sustainable organizational growth and enhance competitiveness within the textile industries sector.